Antibacterial and antibiofilm activities of nonpolar extracts of Allium stipitatum regel. against multidrug resistant bacteria - Karunanidhi, Arunkumar; Ghaznavi-Rad, Ehsanollah; Hamat, Rukman Awang; Pichika, Mallikarjuna Rao; Than, Leslie Thian Lung; Mohd Fauzi, Fazlin; Chigurupati, Sridevi; Belkum, Alex van; Neela, Vasanthakumari (Hindawi Publishing, 2018)
The present study assessed the in vitro antibacterial and antibiofilm potential of hexane (ASHE) and dichloromethane (ASDE) extracts of Allium stipitatum (Persian shallot) against planktonic cells and biofilm structures of clinically significant antibiotic resistant pathogens, with a special emphasis on methicillin-sensitive Staphylococcus aureus (MSSA), methicillin-resistant S. aureus (MRSA), and emerging pathogens, Acinetobacter baumannii and Stenotrophomonas maltophilia. Antibacterial activities were determined through disk diffusion, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), time-kill kinetics, and electron microscopy. Antibiofilm activity was assessed by XTT [2,3-bis(2-methoxy-4-nitro-5-sulfo-phenyl)-2H-tetrazolium-5-carboxanilide] reduction assay and by confocal laser scanning microscopy (CLSM). The zone of inhibition ranged from 13 to 33 mm, while the MICs and MBCs ranged from 16 to 1024 μg mL−1. Both ASHE and ASDE completely eradicated overnight cultures of the test microorganisms, including antibiotic resistant strains. Time-kill studies showed that the extracts were strongly bactericidal against planktonic cultures of S. aureus, MRSA, Acinetobacter baumannii, and S. maltophilia as early as 4 hours postinoculation (hpi). ASHE and ASDE were shown to inhibit preformed biofilms of the four biofilm phenotypes tested. Our results demonstrate the potential therapeutic application of ASHE and ASDE to inhibit the growth of gram-positive and gram-negative biofilms of clinical significance and warrant further investigation of the potential of A. stipitatum bulbs against biofilm-related drug resistance.